Psychosocial and Behavioral Risk Factors of Peptic Ulcer Disease: A Case-Control Study - Kumayl Abbas Meghji; Ayesha Muhammad Ramzan; Areesha Mushtaque Memon; Sidra Rehman; Faiqa Atique; Yousra Arshad Khanzada (Pakistan Journal of Medicine and Dentistry)
Background: Peptic ulcer disease (PUD) is influenced by physiological, psychological, and lifestyle factors. While H. pylori infection and NSAID use are known etiologies, the impact of stress, depression, and unhealthy habits remains underexplored. This study evaluated the association of stress and depression with PUD in Sindh.